Rendimento de cultivares de milho e soja em diferentes zonas agroclimáticas do Paraguai - Teixidó, Blanca Julia Núñez (2013)
The area under soybean production in Paraguay has increased considerably since 1996s. It has increased during 2004\05 as a result of the introduction of transgenic cultivars and seed production of these varieties. The country becomes the fourth largest soybeans exporter in the world. The area estimated soybean production for the 2012/13 season and 3.157.600 ha with a production of 9.367.298 of tons. The area of maize grain in Paraguay has increased considerably since 2002, the estimated maize production for the 2012/13 season was 983.899 ha with a production of 3.935.596 tons. Evaluation of new cultivars to commercial release includes agronomic evaluation for two years in agro-climatic zones of the Eastern Region of Paraguay. Therefore, this study aimed to evaluate the following five soybean cultivars yield, FT20-267, FT20-268, FRO4-179, FRO4-164, FTO3-482 and to compare them to the two reference cultivars (CD 214-RR and EMBRAPA 48). The cultivars were evaluated in South Zone: Bella Vista, (Itapuá department); East Zone: Santa Rita, (Alto Paraná Department) and New Esperanza (Canindeyú Department), Central Zone: Field 9, (Caaguazú Department) and North Zone: Pedro Juan Caballero (Amambay Department). The following five corn hybrids DAS 2B 710, AS 1551, AS 1590, DAS 2B 688, P 30K75 were compared with the reference hybrids DKB 390 and MAXIMUS. They were evaluated in South Zone: Colonia Fran, (Itapuá Department); East Zone: Santa Rita, (Alto Paraná Department) and Yjhovy (Canindeyú Department), Central Zone: Field 9, (Caaguazú Department) and North Zone: Guayaybi, (San Pedro Department). Each plot consisted of four soybean rows of 5.0 m long and 0.45 m spacing between rows. The useful plot area was 3.6 m2 plots with three replications. Yield and weight of 100 seeds were evaluated. The cultivars showed, in general yield and weight of 100 seeds higher or similar to the reference cultivars CD 214-RR and EMBRAPA 48, all cultivars showed yield and weight of 100 seeds higher in Pedro Juan Caballero. Each plot of hybrid consisted of four rows of 5.0 m long with 0.52 m spacing between rows. The useful area was 10.40 m², in three experimental unit replications. In the two years of evaluation (2009 and 2010) of the hybrids showed similar performance to the reference hybrids DKB 390 and MAXIMUS. The Hybrid AS 1551 in out season showed a higher yield compared to other hybrids and also with the references hybrids DKB 390 and MAXIMUS during the two years of evaluation. In 2009 and 2010, the hybrids showed in season and off season, higher yield in Santa Rita in relation to other locations.